High-temperature aqueous corrosion of MO-Na2O-B2O3-SiO2 glass and glass-ceramic coatings on metallic substrates: Effect of alkaline earth metals M2+= {Ca2+, Sr2+, Ba2+} - Otken, Omer Furkan; Ceylan, Iremnur; Cicek, Bugra (ELSEVIER SCI LTD, 2025)
This investigation aims to assess the impact of 2 A alkaline-earth oxides on the alteration of glass/glass-ceramic coatings on steel under conditions of exposure to hot water. Experiments involved integrating CaO, SrO, and BaO into sodium-borosilicate glass systems after that a melting-quenching process to obtain frits. Coated and sinter- crystallized samples denoted as GC-Ca, GC-Sr, and GCC-Ba were exposed to hot aqueous corrosion according to DIN 4753-3 at 95 degrees C, which determined weight loss after 42 days. ICP-MS analyzed aqueous solutions for element leaching. Results indicated that glass-ceramic coatings (GCC-Ba) outperformed glass coating(GC-Ca, GC- Sr). GCC-Ba demonstrated enhanced stability, attributed to limited ion exchange and diffusion at high temperatures, enhancing corrosion resistance, supported by sanbornite crystal phase presence. Total element release by ICP-MS and 42 days of hot water corrosion coatings' weight loss after 42-day corrosion test lined up: GC-Sr > GC- Ca > GCC-Ba.
Keywords: Water corrosion; Chemical resistance; Element release; Migration; Coating; CRYSTALLINE PHASES; BARIUM DISILICATE; BEHAVIOR; ELEMENTS; Materials Science